Vitamin D3 status and seroprevalence of Toxoplasma gondii in reproductive-aged women in Northern Iran - Mostafa Tork (BMC Women's Health, 2025)
Abstract Background Toxoplasma gondii (T. gondii) seropositive is a significant public health concern due to its potential impacts on both general morbidity and specific risks to maternal-fetal health. Concurrently, insufficient Vitamin D3 (Vit D3) levels during gestation may contribute to adverse outcomes for both mother and developing fetus. This study was designed to examine the Vit D3 status and seroprevalence of T. gondii among women of reproductive age in northern Iran. Methods This investigation employed Enzyme-Linked Immunosorbent Assay (ELISA) to quantify anti-T. gondii immunoglobulins (IgG/IgM) and Vit D3 levels in 320 serum specimens from women of reproductive age in northern Iran. Data analysis incorporated prevalence calculations, binary, and multivariate logistic regression for odds ratio determination using SPSS v21. Results A total of 245 out of 320 (76.56%) women of reproductive age were characterized as Vit D3 deficient. Serological analysis revealed a 61.9% (198/320) IgG seroprevalence rate for T. gondii, with only 0.3% (1/320) showing IgM positivity. Notably, 159 seropositive cases (64.8%) occurred among Vit D3-deficient participants. Statistical evaluation demonstrated a significant correlation (OR = 1.71; 95% CI: 1.01–2.88; P = 0.045), indicating 71% increased T. gondii seropositive risk in individuals with insufficient Vit D3 levels compared to those with adequate status. Conclusions This study reveals a high concurrent prevalence of T. gondii infection and Vit D3 deficiency among women of reproductive age in northern Iran. Vit D3 deficiency may be linked to higher susceptibility to infection and potentially to reproductive health issues. However, due to the cross-sectional design of the study, it is not possible to determine whether Vit D3 deficiency increases the risk of infection or if infection itself influences Vit D3 levels. These findings highlight a significant association that warrants further prospective and interventional studies to clarify the direction and underlying mechanisms of this relationship.